Preserved stem cell content and innervation profile of elderly human skeletal muscle with lifelong recreational exercise. (16th March 2022) - Soendenbroe, Casper; Dahl, Christopher L.; Meulengracht, Christopher; Tamáš, Michal; Svensson, Rene B.; Schjerling, Peter; Kjaer, Michael; Andersen, Jesper L.; Mackey, Abigail L.
Abstract : Abstract: Muscle fibre denervation and declining numbers of muscle stem (satellite) cells are defining characteristics of ageing skeletal muscle. The aim of this study was to investigate the potential for lifelong recreational exercise to offset muscle fibre denervation and compromised satellite cell content and function, both at rest and under challenged conditions. Sixteen elderly lifelong recreational exercisers (LLEX) were studied alongside groups of age‐matched sedentary (SED) and young subjects. Lean body mass and maximal voluntary contraction were assessed, and a strength training bout was performed. From muscle biopsies, tissue and primary myogenic cell cultures were analysed by immunofluorescence and RT‐qPCR to assess myofibre denervation and satellite cell quantity and function. LLEX demonstrated superior muscle function under challenged conditions. When compared with SED, the muscle of LLEX was found to contain a greater content of satellite cells associated with type II myofibres specifically, along with higher mRNA levels of the beta and gamma acetylcholine receptors (AChR). No difference was observed between LLEX and SED for the proportion of denervated fibres or satellite cell function, as assessed in vitro by myogenic cell differentiation and fusion index assays. When compared with inactive counterparts, the skeletal muscle of lifelong exercisers is characterised by greater fatigue resistance under challenged conditions in vivo, together with a more youthful tissue satellite cell and AChR profile. Our data suggest a little recreational level exercise goes a long way in protecting against the emergence of classic phenotypic traits associated with the aged muscle. Key points: The detrimental effects of ageing can be partially offset by lifelong self‐organized recreational exercise, as evidence by preserved type II myofibre‐associated satellite cells, a beneficial muscle innervation status and greater fatigue resistance under challenged conditions. Satellite cell function ( in vitro ), muscle fibre size and muscle fibre denervation determined by immunofluorescence were not affected by recreational exercise. Individuals that are recreationally active are far more abundant than master athletes, which sharply increases the translational perspective of the present study. Future studies should further investigate recreational activity in relation to muscle health, while also including female participants. Abstract : Abstract figure legend Lifelong exercisers were studied alongside age‐matched sedentary individuals and young subjects. Muscle biopsies were obtained from all subjects and used for immunofluorescent analyses and cell culture experiments. In vivo measurements of muscle mass and function were also performed. Lifelong exercise was associated with a preserved number of type II myofibre‐associated satellite cells, an improved innervation status that was similar to the young control group, and better muscle function under challenged conditions. The findings suggest that even low amounts of physical activity over many years have a positive impact on muscle health and innervation status. Figure was created using BioRender. Publication licence has been obtained.